Fins & Scales: An Introduction to Bony Fish—A Marine Science Project Book for 4-H Intermediate Members - Karen Blyler (EDIS)
In this project, youth will learn about fish and their adaptations for living in water. This revised 48-page Intermediate level (ages 11-13) project book was written by Karen Blyler, and published by the UF Department of 4-H Youth Development, October 2014.